Murder most grave - McKevett, G. A. (McKevett, G. A. Granny Reid mysteries, 2022)
"With a new grandbaby to care for at home, Stella has little time to spare ... Gallivanting around with her best pal Sheriff Manny Goldford simply isn't an option--until a freshly murdered body is discovered ... Holding a criminal record unlike anyone's, Dexter Corbin was a man who wouldn't be missed ... But he never deserved to meet his end so soon ... When a gravedigger finds Dexter sprawled across the steps of a crypt, Stella and Manny launch into action to investigate who had motive to kill him"--